Factors shaping the dynamics of housing affordability in Australia 2001-11 - Wood, G.; Ong, Rachel; Cigdem, M. (2015)
The models presented in this chapter yield some important findings that are largely in line with Wood and Ong's (2009) earlier findings. However, the current models extend over a longer timeframe and thus uncover some interesting new insights. The models of first spells in unaffordable housing show that most Australians in housing affordability stress escape within a relatively short period of time, though there is evidence of negative duration dependence. Thus, those who fail to exit unaffordable housing quickly find that their chances of escaping housing affordability stress decline sharply as spells lengthen. Mortgagors find it more difficult to manoeuvre out of unaffordable housing than private renters, because the high transaction costs they face impede moves that could ease housing stress. Self- or non-employment also diminish the prospects of evading unaffordable housing circumstances. Sole parents with young dependent children are particularly vulnerable to extended periods in housing affordability stress, as are ethnic groups from non-Englishspeaking backgrounds. While the study timeframe extends across the GFC and post-GFC years, we do not detect a statistically significant impact. Australians in unaffordable housing were perhaps unable to take advantage of lower interest rates and the slowdown in housing markets during the GFC, because it was accompanied by a parallel decline in labour markets, and thus job security. Area-based socio-economic status, as proxied by SEIFA deciles, appears to have a negligible impact on the odds of escaping unaffordable housing. The models of survival in affordable housing confirm that the majority of Australians in affordable housing can expect to sustain it. Furthermore, the models uncover a protective effect as spells in affordable housing lengthen. However, ethnic groups from a non-Englishspeaking background and sole parents with young children are once again more vulnerable, as are self-employed or unwaged persons. Here, job security also becomes important; the odds of surviving in affordable housing is reduced if one is on a part-time fixed-term contract or casual contract. Macro-economic conditions also matter. We find that the chances of sustaining affordable housing have fallen since the GFC.